Risk Mitigation Analysis of Mudharabah Financing at KSPPS BMT Tamzis Bina Utama Branch Magelang City - Adi Fahrudin; Fuad Akhmad Yanuar Rifai; Qurotul Aini (Department of Islamic Banking, 2024)
Financing with mudharabah contracts at KSPPS BMT Tamzis Bina Utama has risks caused by member deviations during financing or negative character of members. This occurs due to member negligence, breach of contract, and internal management of the institution, which can result in losses. Thus it is necessary to mitigate these risks. So, this study uses a qualitative method to look at how the KSPPS BMT Tamzis Bina Utama Magelang City Branch lowers the risks of mudharabah financing. The results of the study indicate that in the process of analyzing financing feasibility, Tamzis has collaborated with PT Pefindo (a credit score that shows the profile of whether members or institutions qualify for financing). Surveys on business feasibility, capacity, collateral, character, capital and economic conditions are also carried out. There are life, health and capital insurance programs (specifically for post-mejeur risk). As for mitigating the possibility of problematic financing, Tamzis has formed a reserve fund whose procedures and amounts follow applicable regulations (DSN Fatwa No: 18 / DSN-MUI / IX / 2000).